Kulishenko L., Yaremenko L. Associative Field of Concept of “Happiness” (on the Basis of Ukrainian Phraseology Units) - L. A. Kulishenko; L. M. Yaremenko (Philological Treatises, 2020)
The article examines the concept of «happiness» in the Ukrainian phraseology. Happiness is the most universal category in the hierarchy of values, one of the main valued priorities of human life. Concept «happiness» is multidimensionalHappiness is determined by both natural and public factors, both biological and social, both family and especially individua. Happiness is subjective, individual on a form experiencing, but objective on maintenance. A word «happiness» has the same root, that word «part». «Happiness» is a kind fate (part) that fell out to the man. The basis is taken paroemìas Ukrainian language because they best reproduce mentality, outlook and essence of the Ukrainian people. In texts of paremiae ideas about «happiness» are personalized and envisaged as an universal model «happiness-man». Found that in people's minds the concept of «happiness» is often revealed by using the lexical paradigms of «happiness-unhappiness». The factors of «happiness» as positive side of vital functions of man always have the opposition – factors of barrier: in ahealth - illnesses, in youth is old age, at welfare are poverties, in freedoms – dependence and others like that. In phraseology units a word «fate» strengthens the value of noun of «happiness» as though, comes forward as an original synonym to him , however a difference is between these concepts, and that is why «happiness» – the positive aspect of «fate» only. In folk consciousness a concept of «happiness» is a multicomponent and multidimensional concept that consists of such elements: physical, moral, material and spiritual, irrational and rational. As a result, the study revealed an associative field, the concept of «happiness», which consists of the following concepts: fortune (luck), health, labor, mind, money (but not wealth), conscience, hope, harmony.